Effects of alloying and pressure on magnetic properties of itinerant intermetallic compound UFe2: Электpонные свойства металлов и сплавов - Panfilov, A. S.; Svechkarev, I. V.; Diko, P.; Mihalik, M.; Zentko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The ferromagnetic state of the itinerant compound UFe2 correlated with a peak in the density of states at the Fermi level is well known to be strongly suppressed by replacing Fe with other 3d elements. To separate the effect of change in filling of the band from that of its deformation under alloying, the magnetic susceptibility of both quasi-binary alloys U(Fe1-xMex)2 (Me = Mn, Co) with a varying number of valence electrons and isoelectronic quasi-ternary alloys U(Fe1-xTx)2, U(Fe0.9-xMn0.1Tx)2 and U(Fe0.9-xCo0.1Tx)2 (T = Mn0.5Co0.5) was studied in the temperature range 4.2 K £ T£300 K. Both the effects were found to play important roles in suppression of the ferromagnetic state in UFe2 -based alloys. In addition, the magnetic susceptibility of U(Fe1-xMnx)2 and U(Fe1-xTx)2 alloys and UCo2 compound have been studied under pressure up to 4 kbar at T = 78 and 293 K. The volume dependence of the exchange enhancement in spin paramagnetism of the UFe2 compound and its alloys has been derived from analysis of the pressure effects in the framework of the Stoner model.